Grafik Kendali Statistik sebagai Instrumen Pemantauan Efisiensi Industri Pelayaran - Megawati, Sintia (Politeknik Negeri FakFak, 2025)
The International Maritime Organization (IMO), as one of the key organizations contributing to the reduction of carbon emissions in the maritime sector, offers several options that maritime industry stakeholders can utilize to measure carbon emissions, one of which is calculating the Energy Efficiency Operational Indicator (EEOI). The statistical x-bar control chart, employed as a monitoring instrument for the EEOI quality parameter, indicates that one container ship trip recorded an EEOI value of 0.00104, which exceeded the upper control limit of 0.00098. The results of process capability analysis on the initial dataset sample revealed that the value of Cp < 1, indicating that energy efficiency performance was not satisfactory. Process control was subsequently applied by eliminating anomalous data, which demonstrated a potential reduction in fuel consumption and EEOI by approximately 25%, as reflected in the improvement of the Cp value. The potential for enhancing the ship’s operational capability, however, still requires further control measures to improve energy efficiency performance. The reduction in fuel consumption directly contributes to lower emission levels, thereby supporting the realization of a sustainable shipping industry.